2019
DOI: 10.1002/cne.24621
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of perinatally born glutamatergic neurons of the mouse olfactory bulb based on NeuroD6 expression reveals their resistance to sensory deprivation

Abstract: During postnatal olfactory bulb (OB) neurogenesis, predetermined stem cells residing in the ventricular–subventricular zone continuously generate progenitors that migrate in the rostral migratory stream and integrate into the OB. Although the vast majority of these postnatally generated interneurons are inhibitory, a sub‐fraction represents glutamatergic neurons that integrate into the superficial glomerular layer. In the present work, we demonstrate that the bHLH transcription factor NeuroD6 is specifically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
(98 reference statements)
2
8
0
Order By: Relevance
“…1HI). As observed before, we found in control condition a slight expansion of the size of the glomerulus and of the distance between neurons [1] and a shrinkage under UNO [12].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…1HI). As observed before, we found in control condition a slight expansion of the size of the glomerulus and of the distance between neurons [1] and a shrinkage under UNO [12].…”
Section: Resultssupporting
confidence: 87%
“…The advent of in vivo two-photon imaging combined with genetic labeling of specific populations allows to unequivocally address this issue. Using this approach, we previously demonstrated that glomerular neuronal populations are differentially affected by UNO since periglomerular glutamatergic interneurons do not undergo cell death under sensory deprivation, while GABAergic neurons do [12]. Here, we followed TH and other GABAergic neurons before, during and after reversible sensory deprivation.…”
Section: Introductionmentioning
confidence: 99%
“…neurons connected to the same glomerulus, whose mechanism and role remain elusive ( 11, 12, 13 ).The glomerular layer is populated by various interneuron subtypes. They are mainly GABAergic, but a small group of glutamatergic interneurons, labeled through the ND6 promoter, project locally in the OB ( 14 ) and could provide a unique opportunity to better understand this glomerular network.…”
Section: Main Textmentioning
confidence: 99%
“…The ND6 promoter drives Cre expression in all glutamatergic neurons in the OB, including the population of vesicular glutamate transporter positive glomerular neurons (Fig. 1B) ( 14 ). We used two-photon calcium imaging in anesthetized animals and recorded consecutively odor-evoked responses in three to six imaging planes in the glomerular layer to sample a larger population of ND6+ neurons (Fig.…”
Section: Main Textmentioning
confidence: 99%
“…S8D ). These distal interacting cEnhancers are marked with open chromatin in excitatory neurons, cells known for high Neurod6 expression 57 . TF motifs enriched at cEnhancers with TF expression patterns that match cEnhancer activity implicated many known brain developmental regulators as activators for these enhancers ( Fig.…”
Section: Introductionmentioning
confidence: 99%